Effect of gaseous ozone treatment on cells and biofilm of dairy Bacillus spp. isolates - Catania, Angela Maria; Dalmasso, Alessandra; Morra, Patrizia; Costa, Emanuele; Bottero, Maria Teresa; Di Ciccio, Pierluigi Aldo (Frontiers in Microbiology, 2025)
Bacillus spp. can produce biofilms and cause recurrent contamination in the food industry. The common clean-in-place (CIP) method is usually employed in sanitizing processing equipment. However, CIP is not always effective in removing biofilms. Ozone represents a promising “green” alternative to control biofilms. In this study, the effect of gaseous ozone (50 ppm) was evaluated in vitro against planktonic and sessile B. cereus and B. subtilis isolates collected from the dairy sector. Planktonic cells were enumerated by plate counts after 10 min, 1 h, and 6 h of ozone treatment. After a short-term (10 min) exposure, a slight reduction in microbial loads (0.66–2.27 ± 0.15 Log10 CFU/mL) was observed for B. cereus strains, whereas a more pronounced reduction (2.90–3.81 ± 0.12 Log10 CFU/mL) was noted in B. subtilis isolates. The microbial load further decreased after 1 h-treatments, around 1.5–3.46 ± 0.11 Log10 CFU/mL for B. cereus strains, and 4.0–5.6 ± 0.11 Log10 CFU/mL for B. subtilis isolates, until complete inactivation of bacterial cells after 6 h of exposure. Moreover, the effect of gaseous ozone treatment (50 ppm, 6 h) was evaluated for its ability to inhibit and eradicate biofilms formed on two common food-contact materials (polystyrene and stainless steel). Sessile B. subtilis cells were the more sensitive to the action of ozone, while a weak effect was highlighted on B. cereus isolates on both surface types. These results were further confirmed by scanning microscopy analysis. The number of cells in the biofilm state was also assessed, showing a not-complete correlation with a decrease in Biofilm Production Indices (BPIs). These findings highlighted the effectiveness of the sanitizing protocol using gaseous ozone in contrasting Bacillus free-living cells, but a not completely counteraction in biofilm formation (inhibition) or eradication of pre-formed biofilm. Thus, the application of ozone could be thought of not alone, but in combination with common sanitization practices to improve their effectiveness.